Bio-control based integrated disease management of basal stem rot disease of coconut - N.B.V. Chalapathi, A. Snehalatharani,; Maheswarappa, C.T. Jose, E. Padma, Rao, G. Ramanandam, H.P. (Journal of Plantation Crops, 2016)
abstract